2007
DOI: 10.1152/ajpheart.01253.2006
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-derived nitric oxide mediates the antiadrenergic effect of human vasostatin-1 in rat ventricular myocardium

Abstract: G. Endothelium-derived nitric oxide mediates the antiadrenergic effect of human vasostatin-1 in rat ventricular myocardium. Am J Physiol Heart Circ Physiol 292: H2906 -H2912, 2007. First published February 9, 2007 doi:10.1152/ajpheart.01253.2006 are vasoactive peptides derived from chromogranin A (CgA), a protein contained in secretory granules of chromaffin and other cells. The negative inotropic effect and the reduction of isoproterenol (Iso)-dependent inotropism induced by VSs in the heart suggest that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
53
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 27 publications
7
53
0
Order By: Relevance
“…In a previous work we showed a PI3K-dependent increase in NO production in VS-1-treated BAE-1 cells [Gallo et al, 2007]. In the present report we observed that VS-1 induces a HSPGs-PI3K-dependent endocytosis of caveolae.…”
Section: Vs-1 Induces a Pi3k And Proteoglycan-dependent Enos Phosphorsupporting
confidence: 73%
See 3 more Smart Citations
“…In a previous work we showed a PI3K-dependent increase in NO production in VS-1-treated BAE-1 cells [Gallo et al, 2007]. In the present report we observed that VS-1 induces a HSPGs-PI3K-dependent endocytosis of caveolae.…”
Section: Vs-1 Induces a Pi3k And Proteoglycan-dependent Enos Phosphorsupporting
confidence: 73%
“…In a recent report we showed that in BAE-1 cells VS-1 induced a PI3K-dependent NO release [Gallo et al, 2007]. To investigate the role of the PI3K pathway also in the VS-1-dependent endocytotic vesicles formation, we performed the FM 1-43 experiments in the presence of the PI3K inhibitor Wortmannin (100 nM).…”
Section: Heparinase and Wortmannin Abolish The Vs-1-dependent Vesiclementioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, the electrophysiological and fluorimetric confocal imaging investigations carried out by Gallo and co-workers on rat papillary muscles and bovine aortic endothelial cells (BAE-1) reveal the major involvement of the endothelium-produced NO and of phosphatidylinositol 3-kinase (PI3K) in transducing the cardiac effects of recombinant human VS-1 (hrSTA-CgA 1-76 ) (Gallo et al, 2007). Therefore, the antiadrenergic effect elicited by VS-1 appears mainly due to a PI3K-dependent NO release by endothelial cells, rather than to a direct action on cardiomyocytes (Gallo et al, 2007). These data were further corroborated by a recent study .…”
Section: Action Mechanism(s) Of Vsmentioning
confidence: 99%